Development of Foresight Leadership Skills for Female Principals of Public Schools in Jeddah from Their Perspective - Mitwalli, Haneen Siraj; Hariri, Randa Ahmed (Journal of Educational and Psychological Sciences, 2025)
This study aimed to investigate the perspectives of female public-school principals in Jeddah on ways to enhance their skills in forward-looking leadership. Furthermore, it is essential to elucidate the notable variations in responses within the study sample as a result of variances in academic credentials and years of professional experience. A quantitative descriptive survey approach was employed, using a questionnaire to gather data from a sample of 261 principals selected through a simple random method out of a total population of 740. The results indicated that school principals highly rated decision-making skills as the most important, followed by strategic planning and human resources management skills. Interestingly, there were no statistically significant differences in responses based on academic qualifications or years of experience. The study recommended that the Education Department conduct seminars, lectures, and workshops to help principals better understand and implement forward-looking leadership practices. Furthermore, specific training courses in strategic planning, decision-making, and human resources management tailored to the needs of principals were also suggested. Overall, the study highlights the importance of continuous development and training for school principals to effectively lead their institutions towards future success.
Keywords: developing ways; school principals' skills; forward-looking leadership